Inoculants containing polymers and endophytic bacteria for the sugarcane crop - Silva, Marinete Flores da; Oliveira, Paulo Janssen de; Xavier, Gustavo Ribeiro; Rumjanek, Norma Gouveia; Reis, Veronica Massena (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effects of field application of inoculants composed of a mixture of diazotrophic bacterial strains and of carboxymethyl cellulose and starch polymers on nitrogen fixation in sugarcane. The experimental design was in randomized blocks in a 4x2 factorial arrangement: four types of nitrogen supply – absolute control, nitrogen control fertilized with 120 kg N (urea) ha-1, polymeric liquid inoculant – IPC 0.8, and polymeric gel inoculant – IPC 2.2; and two sugarcane varieties (RB72454 and RB867515), with split plots (three harvest times – 6, 9 and 11 months after planting), with four replicates. As inoculant vehicles, carboxymethyl cellulose and starch polymers with a 60:40 ratio were tested at 0.8 and 2.2 g L-1 concentrations (IPC 0.8 and IPC 2.2, respectively). The evaluated parameters were stem productivity, total dry matter and nitrogen accumulation. The treatments with the inoculants containing a mixture of diazotrophic bacteria and polymers led to an average increase of 50 and 30 Mg ha-1 in the productivity of the varieties RB72454 and RB867515, respectively, and to an average increase of 18 Mg ha-1 in total dry matter of variety RB867515, in comparison to the absolute control 11 months after inoculation, with no significant difference from the nitrogen control.